The effect of education policy on crime: An intergenerational perspective - Costas Meghir; Mårten Palme; Marieke Schnabel (Institute for Fiscal Studies (IFS), 2011)
The Swedish comprehensive school reform implied an extension of the number of years of compulsory school from 7 or 8 to 9 for the entire nation and was implemented as a social experiment by municipality between 1949 and 1962. A previous study (Meghir and Palme, 2005) has shown that this reform significantly increased the number of years of schooling as well as labor earnings of the children who went through the post reform school system, in particular for individuals originating from homes with low educated fathers. This study estimates the impact of the reform on criminal behavior: both within the generation directly affected by the reform as well as their children. We use census data on all born in Sweden between 1945 and 1955 and all their children merged with individual register data on all convictions between 1981 and 2008. We find a significant inverse effect of the reform on criminal behavior of men and on sons to fathers who went through the new school system.
Keywords: 330; Schulpolitik; Humankapital; Bildungsertrag; Generationengerechtigkeit; Kriminalitätsökonomik; Schweden